A Fetus with Bilateral Polycystic Kidney Disease (Bangladesh Journal of Medical Science, 2026)
Background Autosomal recessive polycystic kidney disease is a rare genetic disorder that can be detected through prenatal ultrasound. Case presentation We presented a 23-year-old mother, gravida 2 at 23 weeks gestation, has been referred to the tertiary hospital for confirmation of the incidental abnormal ultrasonography findings on her growing fetus. Repeat ultrasonography by the maternal-fetal specialist is strongly suggestive of Autosomal Recessive Polycystic Kidney Disease. Given the poor prognosis, the pregnancy was terminated without any complications. Conclusion Our case highlights the value of primary care physicians in early detection and appropriate referral as they are the first point of contact in the healthcare system. We also stress the importance of genetic counseling, which may have an impact on subsequent pregnancies in the family.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 989-992